A comprehensive study on donor‐matched comparisons of three types of mesenchymal stem cells‐containing cells from human dental tissue. (25th November 2018) - Xing, Yixiao; Zhang, Yunpeng; Wu, Xuan; Zhao, Bin; Ji, Yawen; Xu, Xin
Abstract : Background and Objective: Mesenchymal stem cells (MSCs) have been widely used in tissue engineering, such as for regenerating the supporting structures of teeth destroyed by periodontal diseases. In recent decades, dental tissue‐derived MSCs have drawn much attention owing to their accessibility, plasticity and applicability. Dental pulp stem cells (DPSCs), periodontal ligament stem cells (PDLSCs) and gingival MSCs (GMSCs) are the most readily available MSCs among all types of dental MSCs. The purpose of this study was to comprehensively compare the characteristics of MSCs from dental pulp (DP), periodontal ligament (PDL) and gingiva (G) in vitro and thus provide insight into optimizing the performance of cells and seed cell selection strategies for tissue regeneration. Materials and Methods: In this study, patient‐matched (n = 5) cells derived from DP, PDL and G which, respectively, contained DPSCs, PDLSCs and GMSCs were evaluated using multiple methods in terms of their proliferation, senescence, apoptosis, multilineage differentiation and stemness maintenance after long‐term passage. Results: Mesenchymal stem cells‐containing cells from G (MSCs/GCs) showed superior proliferation capability, whereas patient‐matched MSCs‐containing cells from PDL (MSCs/PDLCs) exhibited excellent osteogenic and adipogenic differentiation ability; MSCs‐containing cells from DP (MSCs/DPCs) achieved mediocre results in both aspects. In addition, MSCs/GCs were the least susceptible to senescence, while MSCs/PDLCs were the most prone to ageing. Furthermore, the biological properties of these three types of cells were all affected after long‐term in vitro culture. Conclusion: These three types of dental MSCs showed different biological characteristics. MSCs/PDLCs are the best candidate cells for bone regeneration, but the application of MSCs/PDLCs might be limited to certain number of passages. Improving the differentiation of MSCs/GCs remains the key issue regarding their application in tissue engineering.